Metabolomic Profiling of Tenebrio molitor Reared on Chestnut Shell-Enriched Substrate Using NMR Spectroscopy - Irene Ferri; Mattia Spano; Matteo Dell’Anno; Luisa Mannina; Luciana Rossi (Foods)
The aim of this study was to evaluate the metabolomic profile of T. molitor larvae reared on the following innovative growth substrates: wheat bran (control, CTRL); wheat bran supplemented with 12.5% w/w chestnut shell (TRT1); and wheat bran supplemented with 25% w/w chestnut shell (TRT2) for 14 days of trial. At the end of this experiment, larvae were transformed into insect meals for nutritional characterization. Nuclear Magnetic Resonance (NMR) spectroscopy was carried out to evaluate the metabolomic profile of organic acids, sugars, nitrogen bases and derivates, fatty acids, and other compounds. Chemical analysis showed an increased level of crude protein in TRT1 compared to CTRL and TRT2 (p = 0.0391). The metabolite profiles of TRT1 and TRT2 were similar to each other but distinct from those of the CTRL group. Notably, larvae enriched with chestnut shells revealed the presence of uracil, uridine, and glucose, while fumarate was absent. The enrichment analysis showed that in TRT1 and TRT2, the glyoxylate and dicarboxylate metabolism was more relevant compared to CTRL. These findings indicate that chestnut shell inclusion affects the larvae metabolism of T. molitor and demonstrates the effectiveness of NMR spectroscopy in revealing a relation between insect metabolism and growth substrate.